Rethinking Indoor Wireless: Low Power, Low Frequency, Full-duplex - Radunovic, Bozidar; Gunawardena, Dinan; Key, Peter; Proutiere, Alexandre; Singh, Nikhil; Balan, Horia Vlad; DeJean, Gerald (Microsoft Research, 2009)
Existing indoor WiFi networks in the 2.5GHz and 5 GHz use too much transmit power, needed because the high carrier frequency limits signal penetration and connectivity. Instead, we propose a novel indoor wireless design paradigm, based on Low Frequency, using the newly freed white spaces previously used as analogue TV bands, and Low Power – 100 times less power than currently used. Preliminary experiments show that this maintains a similar level of connectivity and performance to existing networks. We also advocate full-duplex networking in a single band, which becomes possible in this setting (because we operate at low frequencies). It potentially doubles the throughput of each link and eliminates hidden terminals.